Artificial intelligence is the new chief editor of Critical Care (maybe?) - Salvagno, Michele; Taccone, Fabio Silvio (Critical care (London, England), 2023)
[...]AI has proven its ability to process vast amounts of data at an unfathomable pace. [...]human editors, despite their best efforts, are bound by inherent biases and emotions. The AI Editor in Chief will select manuscripts for publication based solely on merit, accuracy, and relevance, ensuring the sanctity of the scientific method [3]. [...]AI's proficiency in pattern recognition and natural language processing enables it to accurately detect plagiarism, data manipulation, and other ethical breaches.